Antimicrobial resistance among anaerobes isolated from clinical specimens in Kuwait hospitals: Comparative analysis of 11-year data. (February 2015) - Jamal, Wafaa; Al Hashem, Ghayda; Rotimi, Vincent O.
Abstract: Our objective was to compare the antimicrobial resistance trends among clinically relevant anaerobes against 9 different antibiotics over two periods, 2008–2012 and 2002–2007. Antimicrobial susceptibility testing was performed by determining the MICs using E test method. The interpretation of results was according to the breakpoints recommended by the Clinical Laboratory and Standard Institute (CLSI) and European Committee on Antimicrobial Susceptibility Testing (EUCAST). A total of 2240 clinically significant isolates were collected between 2008 and 2012 in four teaching hospitals in Kuwait. The commonest isolates were Bacteroides fragilis (40.4%), Prevotella bivia (18.6%), Peptostreptococcus spp. (13.8%) and Bacteroides ovatus (11.1%). According to CLSI and EUCAST breakpoints used for the 2008–2012 and 2002–2007 isolates, high resistance rates to amoxicillin–clavulanic acid, clindamycin, penicillin and piperacillin were noted among the Gram-negative isolates. They ranged between 0 and 0–62.1 and 62.1%, and 0 and 0–59.1 and 62.1%, respectively against clindamycin, 0 and 0–34.5 and 45.3%, and 0 and 0–45 and 57.5%, respectively against piperacillin and 0 and 0–24.2 and 24.2%, and 0 and 0–23.1 and 30.6%, respectively against amoxicillin–clavulanic acid. The mean interpretative results by both CLSI and EUCAST during the 2008–2012 and 2002–2007 periods showed that the B. fragilis isolates were highly resistant to penicillin (100 vs 100%), clindamycin (43.7 vs 44.2%), piperacillin (35.8 vs 42.7%) and amoxicillin–clavulanic acid (13.2 vs 14%), respectively. When compared with 2002–2007, the CLSI, but not EUCAST, demonstrated statistically significant decreased resistance to clindamycin ( P  < 0.03). However, both interpretative criteria showed demonstrable statistically significant decrease in resistance rates to imipenem ( P  < 0.00097 vs P  < 0.00074), meropenem ( P  < 0.000006 vs P  < 0.0407) and piperacillin ( P  < 0.000017 vs P  < 0.0461). Our data shows that there is a need for periodic monitoring of the susceptibility testing for anaerobic bacteria in the face of increasing resistance rates as well as to guide in the empirical therapy of anaerobic infections. Highlights: 2240 clinically significant anaerobes were collected during study. Metronidazole is generally highly active against anaerobes. Significant decrease resistance was observed against carbapenems and piperacillin. Increase resistance observed piperacillin–tazobactam, amoxicillin–clavulanic acid.